Two-Factor Authentication Model - Reyes Riveros, Anderson Jhanyx (2023)
The main objective of this paper is the development of a model that allows the authentication of a user for access control using the Two-Factor Authentication model. For the development of such a model we present a secure two-factor authentication (TFA) scheme based on the user's possession of a password and a cryptographically capable device. The security of this model is end-to-end in the sense that whoever wants to access in a fraudulent way is going to find it difficult and thus guarantee the security of the user of the system, the algorithm used was Cryptographic Networks, which is a double authentication model. Also the programming language cakephp 4.0 was used, in addition to using the visual studio code program to perform the algorithms required for the double authentication model to work.